Survival assessment of the extended‐wear insulin infusion set featuring lantern technology in adults with type 1 diabetes by the glucose clamp technique. Issue 6 (4th March 2021) - Simic, Amra; Schøndorff, Pernelle K.; Stumpe, Tobias; Heschel, Matthias; Regittnig, Werner; Pöttler, Tina; Ninaus, Daniela; Augustin, Thomas; Groselj‐Strele, Andrea; Pieber, Thomas R.; Mader, Julia K.
Abstract: Maintaining good glycaemic control with the same infusion set for longer than 3 days may improve the quality of life of insulin pump users. The aim of the current study was to assess the efficacy and safety of the novel, extended‐wear infusion set over 7 days of wear in adults with type 1 diabetes. Sixteen participants completed three identical 8‐hour euglycaemic clamp experiments on Days 1, 4 and 7 of infusion set wear. Between the experiments, the participants were discharged home for routine diabetes management while wearing the same extended‐wear infusion set throughout the study. Time to reach the maximum glucose infusion rate (TGIRmax ) on Day 7 was reduced by 67% compared with Day 1 ( p < .001). The corresponding area under the glucose infusion rate curve (AUCGIR ) was comparable for the first 2 h of the clamp ( p = .891) but decreased by 28% over time ( p < .008). While the extent of insulin absorption decreased with prolonged wear, it was accompanied by an increase in insulin absorption rate. The infusion set survival rate was 100% without leakages, occlusion alarms, severe hypoglycaemia or ketoacidosis. The extended‐wear infusion set proved safe and effective during prolonged wear in real‐life conditions.